Cladosporium cladosporioides keratomycosis : a case report. - Chew, Fiona L. M.; Subrayan, Visvaraja; Chong, Pei Pei; Goh, Meng Chuan; Ng, Kee Peng (Springer, 2009)
Keratomycosis is a frequent cause of ocular morbidity and blindness. Filamentous fungi such as Fusarium and Aspergillus have been reported to be leading causes of keratomycosis in India1 and China.2 Keratomycosis caused by Cladosporium cladosporioides, a pigmented ﬁ lamentous fungus, is very rare. We report a case of Cladosporium cladosporioides keratomycosis identiﬁ ed by polymerase chain reaction (PCR) and DNA typing.